An optimal design to provide combined cooling, heating, and power of residential buildings. (2nd October 2018) - Keynia, Farshid
Abstract: Providing electricity for the residential buildings which devote a high portion of energy consumption is very crucial all over the world. Not only electrical loads but also heating and cooling loads are required to be supplied in a building. The aim of this paper is to supply cooling, heating, and electrical loads in a building by separating generation system and cogeneration system. In this regard, the optimal problem was developed to minimize the total costs using particle swarm optimization algorithm. As a numerical study, a high-rise building with 72 units located in Kerman is analyzed for eight different scenarios.The results show that in order to supply cooling, heating, and power, a cogeneration system consisting of a 195 kW micro gas turbine as prime mover, a 281 kW single-effect absorption chiller, a 439 kW air cooling compaction chiller, an 187 kW auxiliary boiler to compensate the heat load, and a 52.8 kW photovoltaic to generate employed electrical loads, is the best optimal system to supply the base building loads. In this optimized system, the annual electricity sales revenue is 93, 251$, the annual cost of buying power is 7001$, the cost of buying fuel as annual consumption is 15, 852.4$, and the annual production of carbon dioxide emissions in the building is 229.78 tons. The return on investment period for the aforementioned project is also estimated 4.98 years.